2021
DOI: 10.1016/j.numecd.2021.05.031
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 lockdown as an opportunity to change lifestyle and body weight in people with overweight/obesity and diabetes: Results from the national French COVIDIAB cohort

Abstract: Background and aims: To analyze lifestyle habits and weight evolution during the COVID-19 pandemic-associated lockdown, in diabetes and overweight/obesity patients (body mass index (BMI) [25e29.9] and !30 kg/m 2 , respectively). Methods and results: We collected information on participants' characteristics and behavior regarding lifestyle before and during the lockdown, through the CoviDIAB web application, which is available freely for people with diabetes in France. We stratified the cohort according to BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…First, our results on increasing exercise among people with diabetes in a higher proportion than healthy individuals are consistent with previous findings [23] , [41] . A possible explanation is that individuals with diabetes, aware of their vulnerability, likely try to protect themselves [42] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…First, our results on increasing exercise among people with diabetes in a higher proportion than healthy individuals are consistent with previous findings [23] , [41] . A possible explanation is that individuals with diabetes, aware of their vulnerability, likely try to protect themselves [42] .…”
Section: Discussionsupporting
confidence: 93%
“…We observed unstable BMI trends among people with diabetes, who experienced both weight loss and gain [11] . Reduced alcohol consumption is in line with other analyses [23] and could be explained with an effort towards better nutrition. In accordance with existing literature [22] , results for psychiatric symptoms were inconclusive.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For alcohol, Binhardi et al (39) and Ghosh et al (45) reported that modal responses were no alcohol consumption or no change in alcohol consumption, respectively. Hansel et al (47) and Sacre et al (36) reported no change in alcohol consumption. For smoking, Utli et al (60) and Ghosh et al (45) reported no smoking as the modal response.…”
Section: Resultsmentioning
confidence: 96%